O efeito da violência contra a mulher sobre os filhos - Kulka, Terezinha (2017)
The main objective of this study was to verify the effect of violence against women on their children. The participants of the survey were 30 women and their children (43), all housed in a shelter for victims of domestic violence who are under protective measures, according to what the Maria da Penha Law advocates. Individual interviews with all participants were carried out and the following instruments were applied: Inventory of Parenting Styles, Beck Depression Inventory, Beck Anxiety Inventory, PCL-L - Adult Behavior Checklist, YSR - Youth Self Report. The quantitative results show that there is a tendency for correlations between anxiety and depression states in the sampled mothers and the levels of anxiety, depression and internalizing problems of the children. Likewise, the posttraumatic stress levels of the offspring are correlated with the posttraumatic stress levels of the mothers. Data analysis showed that there is no correlation between the time of coexistence of women with violence with a mean of 9.85 years with PD 7.97 with PCL-C, BAI, BDI. The qualitative analysis through the qualitative results and the construction of the Collective Subject Discourse, showed that the IPV causes impacts on the mother with effect on the children. Regarding the frequency of the occurrence of IPV, it was found that it occurs daily in 48.28% and 37.93% in the population surveyed weekly. The children's answers pertaining to the question, what do you do when the parent / stepfather assaults the mother, 53.85% reported that: they testify and 46.15% interfere. Of the adolescents 36% who testify, 48% interfere, 18% protect the siblings. In the observation of women, boys react with fear, frightened 26.67% "anger", hostility 23.33% and 50% interfere and as for girls 56.67% afraid, frightened. Also 46.15% of the children answered that they feel protected from the BTI with the maternal grandmother and 42% of the adolescents in the school. The children responded that scenes of violence are remembered in 96.15%, and 88.50% of adolescents. 69.75% of the adolescent and 28% of the children answered that they have bad thoughts about the aggressor. Therefore, both analyzes demonstrated that children / adolescents in the context of BTI are repeatedly revivified and co-occurring with maltreatment, putting them at risk and living with several stressors, causing violence / polyvictimization both In boy as in girl.